Efficacy of varicose vein surgery with preservation of the great safenous vein - Bernardo Cunha Senra Barros (Revista do Colégio Brasileiro de Cirurgiões)
OBJECTIVE: To evaluate the efficacy of surgical treatment of varicose veins with preservation of the great saphenous vein. METHODS: We conducted a prospective study of 15 female patients between 25 and 55 years of age with clinical, etiologic, anatomic and pathophysiologic (CEAP) classification 2, 3 and 4. The patients underwent surgical treatment of primary varicose veins with great saphenous vein (GSV) preservation. Doppler ultrasonography exams were carried out in the first and third months postoperatively. The form of clinical severity of venous disease, Venous Clinical Severity Score (VCSS) was completed before and after surgery. We excluded patients with history of deep vein thrombosis, smoking or postoperatively use of elastic stockings or phlebotonics. RESULTS: All patients had improved VCSS (p <0.001) and reduction in the diameter of the great saphenous vein (p <0.001). There was a relationship between VCSS and the GSV caliber, as well as with preoperative CEAP. There was improvement in CEAP class in nine patients when compared with the preoperative period (p <0.001). CONCLUSION: The varicose vein surgery with preservation of the great saphenous vein had beneficial effects to the GSV itself, with decreasing caliber, and to the symptoms when the vein had maximum caliber of 7.5 mm, correlating directly with the CEAP. The decrease in GSV caliber, even without complete abolition of reflux, leads to clinical improvement by decreasing the reflux volume.